Use of telemedicine for follow-up of lupus nephritis in the COVID-19 outbreak: The 6-month results of a randomized controlled trial. (April 2022) - So, Ho; Chow, Evelyn; Cheng, Isaac T; Lau, Sze-Lok; Li, Tena K; Szeto, Cheuk-Chun; Tam, Lai-Shan
Objective: This study aimed to evaluate the short-term patient satisfaction, compliance, disease control, and infection risk of telemedicine (TM) compared with standard in-person follow-up (FU) for patients with lupus nephritis (LN) during the COVID-19 pandemic. Method: This was a single-center open-label randomized controlled study. Consecutive patients followed at the LN clinic were randomized to either TM or standard FU (SF) group in a 1:1 ratio. Patients in the TM group received FU via videoconferencing. SF group patients continued conventional in-person outpatient care. The 6-month data were compared and presented. Results: From June to December 2020, 122 patients were randomized (TM: 60, SF: 62) and had at least 2 FUs. There were no baseline differences, including SLEDAI-2k and proportion of patients in lupus low disease activity state (LLDAS), between the two groups except a higher physician global assessment score (PGA) in the TM group. After a mean FU of 19.8 ± 4.5 weeks, the overall patient satisfaction score was higher in the TM group. More patients in the TM group had hospitalization (15/60, 25.0% vs 7/62, 11.3%; p = .049) with higher baseline PGA (OR = 1.17; 95% CI, 1.08–1.26) being the independent predictor. The proportions of patients remained in LLDAS were similar in the two groups (TM: 75.0% vs SF: 74.2%, p = .919). None of the patients had COVID-19. Conclusions: TM FU resulted in better patient satisfaction and similar short-term disease control in patients with LN compared to standard care. However, it was associated with more hospitalizations and might need to be complemented by in-person visits especially in patients with higher PGA.